On conditionless bases of the kernels generated by differential equations of the second order - Levchuk, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish necessary and sufficient conditions for a system of functions generated by differential equations of the second order to be a basis. Our method is based on the application of the Muckenhoupt condition.